(untitled) - Spencer, Edgar W. (Boston, 2003)
Earth Science: Understanding Environmental Systems is intended for introductory courses in Earth Science and Earth Systems Science, which place emphasis on the systems approach to earth science with special attention to the impact these systems have on the environment. It is appropriate for non-science majors with no previous college science or mathematics courses
Keywords: Earth sciences